Role of Tongue Print Examination in Forensic Odontology Identification - Rusmaputeri, Fadhilah; Auerkari, Elza Ibrahim (Newinera Publisher, 2025)
The tongue is a part of the oral cavity that is easy to examine. The tongue is very well protected from the external environment so that it can be adequately examined even though some other body organs have been damaged. The tongue has identical characteristics in each individual, so it can be used to identify a person. Several studies have been conducted, it has been found that there is a tendency for particular features of the shape, size, and structure of the tongue to be different in men and women. Therefore, it can be utilized by forensic odontologists as a support in an individual identification process.